2006
DOI: 10.1111/j.1469-7610.2006.01630.x
|View full text |Cite
|
Sign up to set email alerts
|

The Croydon Assessment of Learning Study: Prevalence and educational identification of mild mental retardation

Abstract: The current study produced a high estimate of the prevalence of mild intellectual disability based on the WISC but not on the CAT. The findings highlight that the majority of mild intellectual disability in the UK would not be detected using registers. Cases that are detected by registers are more behaviourally disturbed than others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…However, other diagnoses were also comorbid with ADHD, including anxiety (38.7 %), conduct disorder (14.3 %), and affective disorder (3.8 %). Among children with ADHD and ID, comorbidity appears to be even more common than compared to typically developing children with ADHD (Baker et al 2010;Neece et al 2011;Neece et al 2013;Simonoff et al 2006). In our own work we have found that similar to previous findings with typically developing samples, ADHD and ODD are the two most common co-occurring disorders (Baker et al 2010;Neece et al 2011;Neece et al 2013).…”
Section: Attention-deficit Hyperactivity Disorder In Children With Idsupporting
confidence: 79%
“…However, other diagnoses were also comorbid with ADHD, including anxiety (38.7 %), conduct disorder (14.3 %), and affective disorder (3.8 %). Among children with ADHD and ID, comorbidity appears to be even more common than compared to typically developing children with ADHD (Baker et al 2010;Neece et al 2011;Neece et al 2013;Simonoff et al 2006). In our own work we have found that similar to previous findings with typically developing samples, ADHD and ODD are the two most common co-occurring disorders (Baker et al 2010;Neece et al 2011;Neece et al 2013).…”
Section: Attention-deficit Hyperactivity Disorder In Children With Idsupporting
confidence: 79%
“…In addition, the study only focused on children aged 8 or older. While some individuals may not receive a diagnosis of intellectual disability until they are teenagers (Simonoff et al, 2006) or even adults (Hamilton, 2006), earlier identification of those children who are likely to have an intellectual disability would be preferable. Research does, however, indicate that accurate screening of young children is difficult to achieve (Bornholt, Spencer, Ouvier, & Fisher, 2004;Sonnander, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Research does, however, suggest common difficulties that are shared by many people with an intellectual disability (Emerson, Hatton, Bromley, & Caine, 1998), including with working memory (Schuchardt, Gebhardt, & Mäehler, 2010) and understanding more abstract concepts such as time (Owen & Wilson, 2006). As a result, many children with an intellectual disability may require some additional support in relation to areas such as education (Simonoff et al, 2006), relationships (Heiman, 2000) and behaviour (Rzepecka, McKenzie, McClure, & Murphy, 2011). The family may also require support, as research suggests that having a child with an intellectual disability can impact on the family unit.…”
Section: Introductionmentioning
confidence: 99%
“…However, prevalence estimates show a high degree of variation around the expected value, ranging from 1-8% (134,150,166). This spread is far more obvious for mild ID (IQ 70-50) than for severe ID (IQ < 50).…”
Section: Definition and Prevalencementioning
confidence: 91%